2015
DOI: 10.1186/s12943-015-0338-9
|View full text |Cite
|
Sign up to set email alerts
|

MiR-377 targets E2F3 and alters the NF-kB signaling pathway through MAP3K7 in malignant melanoma

Abstract: BackgroundThe incidence of cutaneous malignant melanoma continues to rise, and once the disease metastasizes it is almost inevitably fatal. We recently reported that a large miRNAs cluster on human chromosome 14q32, implicated in many types of cancers, is significantly down-regulated in melanoma. miR-377, one of the miRNAs located within this cluster, was studied here.MethodsqRT-pCR was used to quantify miR-377 levels in melanoma cell lines and samples. Melanoma cell lines ectopically expressing miR-377 were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
63
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 59 publications
2
63
0
1
Order By: Relevance
“…In our study, we investigated the effect of NEAT1 on NSCLC cells and discovered that NEAT1 involved in the ceRNA regulatory network and functioned as endogenous miRNA sponges to bind to miR-377-3p and regulated its function [71]. Recent studies indicated miR-377 showed tumor suppressive role on malignant melanoma [72], human clear cell renal cell carcinoma (CCRCC) [73], and hepatocellular carcinoma [74], while its role on NSCLC had not been investigated. In this study, we found miR-377-3p was down-expressed in NSCLC lung tissues and cell lines, and miR-377-3p suppressed cell growth, metastasis, and induced cell apoptosis in A549 and H1299 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we investigated the effect of NEAT1 on NSCLC cells and discovered that NEAT1 involved in the ceRNA regulatory network and functioned as endogenous miRNA sponges to bind to miR-377-3p and regulated its function [71]. Recent studies indicated miR-377 showed tumor suppressive role on malignant melanoma [72], human clear cell renal cell carcinoma (CCRCC) [73], and hepatocellular carcinoma [74], while its role on NSCLC had not been investigated. In this study, we found miR-377-3p was down-expressed in NSCLC lung tissues and cell lines, and miR-377-3p suppressed cell growth, metastasis, and induced cell apoptosis in A549 and H1299 cells.…”
Section: Discussionmentioning
confidence: 99%
“…NFκB has been shown to induce EMT via induction of vascular endothelial growth factor (VEGF) expression and receptor translation, increase of MMP expression, and promotion of Snail [26,96]. In addition, overexpression of NFκB and increased localization of NFκB to the nucleus have been associated with faster migration of melanoma cells, and miRNA inhibition of targets directly upstream of NFκB has been shown to reduce melanoma cell migration [97,98]. Recent evidence suggests that NFκB promotes invasion by stabilizing favorable transcription factors.…”
Section: Transcription Factors Of Emtmentioning
confidence: 99%
“…Stable expression of miR-377 diminished the proliferative, migratory, and the colony-forming capability of melanoma cell lines. 33 Down-regulation of miR-1184 was stated in rectal cancer. 34 However, no other reports are available in cancer cases, suggesting the deregulation of miR-5587 and miR-4687.…”
Section: Discussionmentioning
confidence: 99%
“…More than 200 different HPV types are identified, which includes the carcinogenesis promoting high-risk HPV types (HR-HPV) such as HPV types 16,18,31,33,35,39,45,51,52,56,58,59, and 68. Among HR-HPV types, HPV type 16 is the common oncogenic type followed by HPV type 18.…”
mentioning
confidence: 99%